Students’ Perspectives on Peer Oral Corrective Feedback Strategies in Higher Education : Mixed Method Research in the Finnish Context - Shaltaeva, Elizaveta (My University, 2024)
Understanding students' beliefs and perspectives is crucial in a language learning environment. As communication and oral corrective feedback (OCF) happen not only in teacher-student, but also in peer interaction, learners’ perspectives on feedback strategies are important to consider. This study aims to investigate these perspectives within the Finnish university context and examine the impact of their background variables on the preferences for peer OCF strategies. This research also compares the perspectives on peer and teacher OCF strategies. This work complements the author’s major thesis (Shaltaeva 2024), which focuses on teacher OCF, by specifically exploring peer OCF to provide a more comprehensive view of students’ perspectives on OCF strategies. A mixed-method design guides this research. It combines quantitative findings from surveys and qualitative data obtained via interviews. The quantitative data is based on the responses of 104 students who attended academic English courses at the University of Turku, while the qualitative data was collected through five interviews. The analyses demonstrate that university students show a general preference for recasts, explicit correction and metalinguistic feedback. Clarification requests, repetition, and elicitation rank lowest among feedback strategies. Notably, some students' preferences differ from the overall trend. Moreover, feedback strategy choices vary based on the type of correct mistake. The study also uncovers gender differences, with female students demonstrating a more positive attitude toward recasts, while no differences have been found across English proficiency levels or academic faculties. When comparing peer and teacher feedback, students show a more positive attitude toward metalinguistic feedback used by a teacher and clarification requests and repetition used by a peer. The research highlights the importance of acknowledging and addressing individual preferences rather than focusing on common tendencies in an educational setting.
Keywords: corrective feedback, oral corrective feedback, oral corrective feedback strategies, peer oral corrective feedback, teacher oral corrective feedback, students’ perspectives, students’ preferences, students’ beliefs, second language learning